The Philippine urban poor - Doherty, John F.; Aquino, Belinda A.; University of Hawaii at Manoa. Philippine Studies Program (Honolulu, Hawaii Philippine Studies Program, Center for Asian and Pacific Studies, University of Hawaii, 1985)
"This occasional paper aims to provide an outlet for scholarly work on Philippine-related topics. The series is broadly interdisciplinary but manuscripts touching on specialized subjects on the humanities, social sciences, and other aspects of Philippine life and culture will also be considered."--Foreword
I. the Metro Manila squatters and the martial law regime -- II. the urban labor force -- III. Small fishermen.
"June 1985."
Includes bibliographical references.
Fi-12293g donated by Prof. Mamoru Tsuda
Keywords: Urban poor -- Philippines; Philippines -- Economic conditions; Philippines -- Social conditions